1984
DOI: 10.1103/physreva.30.812
|View full text |Cite
|
Sign up to set email alerts
|

Xe5s,5pcorrelation satellites in the region of strong interchannel interactions, 28—75 eV

Abstract: The Xe 5s,5p photoelectron satellite spectrum has been studied in the photon-energy range from 28 to 75 eV with the aid of synchrotron radiation. This range includes the Xe 5s Cooper minimum, and the cross sections and angular distribution data demonstrate the importance of the strong twoelectron channels in the region where the Ss cross section is small. Although the behavior of the satellites was not recorded over the 4d maximum, the data near 75 eV show an enhancement in the cross section in that region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 23 publications
7
39
2
Order By: Relevance
“…To describe the PR process of Xe, we need to use the PR transition dipole moment including multielectron effects in QRS theory. Such PR moment can be extracted from the experimental photoionization cross section (PICS) [40,41]. In the calculation, we incorporate the PICS of Xe, which is extended into high-photon energy region (a few hundred eV), using the relativistic random-phase approximation (RRPA) by Kutzner et al [42].…”
mentioning
confidence: 99%
“…To describe the PR process of Xe, we need to use the PR transition dipole moment including multielectron effects in QRS theory. Such PR moment can be extracted from the experimental photoionization cross section (PICS) [40,41]. In the calculation, we incorporate the PICS of Xe, which is extended into high-photon energy region (a few hundred eV), using the relativistic random-phase approximation (RRPA) by Kutzner et al [42].…”
mentioning
confidence: 99%
“…The quantum efficiency of the AXUV-100 photodiode was also factored in. The Xe cross-section data were obtained from Samson and Stolte [37] and Fahlman et al [38]. The transmission calibration procedure has been discussed in more detail by Niskanen et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…The spectra are considerably better resolved than earlier published work using PES at similar photon energies (1 6, 17) or XPS (5,6) with the peaks a, b, c, d, e, f, g, h, and i not having been resolved previously. Fahlman et al (59,60) have also reported Xe 5 s PES spectra at quite good energy resolution, and also obtained angular distribution information over the photon-energy range 28.5-74. intensities. Figure 6 shows a theoretical spectrum obtained using the intensities as calculated by Hansen and Persson using CI methods (27,45) and convoluted with the experimental energy resolution (0.34 eV).…”
Section: Introductionmentioning
confidence: 99%
“…The energies of the spectral features in Fig. 8 are given in Table 4 together with low-photon-energy, high-resolution PES data (59)(60)(61). From a comparison of the presently obtained higher-resolution Xe spectra (Fig.…”
Section: Xe 5 S Spectrummentioning
confidence: 99%